Assessment of risks in conditions of provision of security of economic activities of organizations - Polozova, T.; Cherkashina, M.; Shapoval, O.; Romanchik, T. V.; Alzoubi, Laith Abdel Karim Mohammad (General Jonas Žemaitis Military Academy of Lithuania, 2019)
The study of the evolution of the economic security of the business entity has shown that at the present stage of economic development it is important to consider the factors of influence on economic security, in particular: the effectiveness of management, personnel and financial safety, a strategic approach to the functioning of the communication system of protection, taking into account the evolution of security and active search for innovative modern domains of development of industrial organizations and increase of the responsibility of performers for the consequences of their work. This allows to reduce the risk of loss of economic safety of the business entity. It was argued that innovative conceptualization of risk as a probable threat of losses lies within the scope of activity of managers of various units and has features of probable economic and objective-subjective nature, as well as a wide range of variability of the impact on the issues of economic safety and is conditioned by the dynamic development of important societal significant economic processes at the global and national levels, which ultimately contributes to enhancement of the organization’s competitive advantages.
Keywords: risk management; economic safety; mechanism of minimization; event occurrence probability; financial position